- 1-800-665-6601
- [email protected]

together. Polynomial multiplication is product of two terms into one term polynomial. Multiplication of two

polynomials involves that multiply each term in one polynomial with each term in another polynomial and

group the like terms to get simplified form.

Solution Steps:

Here we can use the FOIL method to solve this problem. FOIL stands for First, Outer, Inner and Last. In this

order multiplication is done to get the answer.

=(2x+5)(x-3)

=2x(x-3)+5(x-3)

=2x(x) +2x(-3) +5(x)+5(-3)

=2x^2-6x+5x-15

=2x^2-x-15.

Answer is 2x^2-x-15.

Solution steps:

Here we can use the FOIL method to solve this problem. FOIL stands for First, Outer, Inner and Last. In this

order multiplication is done to get the answer.

=2a(3a-2b+c)-b(3a-2b+c)

=2a(3a)+2a(-2b)+2a(c)-b(3a)-b(-2b)-b(c).

=6a^2-4ab+2ac-3ab+2b^2-bc

Add or subtract like terms

=6a^2-7ab+2ac+2b^2-bc

Rewrite the equation as

=6a^2-7ab-bc+2ac+2b^2.

Answer is 6a^2-7ab-bc+2ac+2b^2.